1998
DOI: 10.1080/02827589809382981
|View full text |Cite
|
Sign up to set email alerts
|

On the potential of Kriging for forest management planning

Abstract: Forest management planning aims at fulfilling the overall goals for the forest owner. The economic optimal scheduling of treatments in spatially discrete forest stands, the time dimension, has been thoroughly investigated in research. The spatial dimension is less investigated. Normally, spatially discrete stands are defined as treatment units. These are inventoried using subjective methods with unknown precision. As an alternative to this conventional way to describe the forest, the present investigation used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 6 publications
0
22
0
2
Order By: Relevance
“…Gunnarson et al (1998) e Tuominen et al (2003 relataram que estimativas baseadas em correlação espacial não são eficientes em florestas manejadas ou exploradas, pois intervenções humanas causam mudanças abruptas, sendo a krigagem indicada para florestas naturais não manejadas e plantações florestais. Porém, isso está em desacordo com os preceitos do manejo florestal, pois as modificações na estrutura da floresta dele decorrentes não podem ser alterações de grande magnitude.…”
Section: Discussionunclassified
“…Gunnarson et al (1998) e Tuominen et al (2003 relataram que estimativas baseadas em correlação espacial não são eficientes em florestas manejadas ou exploradas, pois intervenções humanas causam mudanças abruptas, sendo a krigagem indicada para florestas naturais não manejadas e plantações florestais. Porém, isso está em desacordo com os preceitos do manejo florestal, pois as modificações na estrutura da floresta dele decorrentes não podem ser alterações de grande magnitude.…”
Section: Discussionunclassified
“…Spatial interpolation methods (especially kringing) have been previously argued as unsuitable for assessment purposes in managed forests (Akhavan et al 2010). On the other hand, several studies have reported successful application of such methods in homogenous natural forest areas (Gunnarsson et al 1998, Tuominen et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional management planning, stands are defined through the planning process. The type of of the management objectives is a component of this process (Gunnarsson et al 1998). However, the use of computers has changed this conventional approach, and spatially and temporally dynamic description and treatment units can readily be produced (Holmgren & Thuresson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their value for forest management planning has been considered low (e.g. Holmgren & Thuresson 1998). One reason suggested for the high stand-and plot-level estimation errors is the low spatial resolution of the satellite image material employed.…”
Section: Remote Sensing Imagerymentioning
confidence: 99%
“…Kriging has been applied in estimating forest variables in forest management planning, e.g. by Holmgren and Thuresson (1997) and Gunnarsson et al (1998). The use of geostatistical methods begins by studying the spatial variation of the variables to be estimated.…”
Section: Geostatistical Interpolation (V)mentioning
confidence: 99%